Understanding The Causes And Treatments Of Bipolar Disorder And Related Disorders Through Genome Sequence Analysis - Agarwal, Kavita; Nagpal, Tapsi; Mishra, R. P. (Migration Letters, 2024)
It has only been demonstrated that a small percentage of the heritability of bipolar disorder (BD) is due to genetic factors. This has led to an attempt to reduce the heterogeneity of BD by focusing on sub-phenotypes of BD, such as treatment response. The objective of this study’s investigations was to find molecular signatures associated with bipolar disorder (BD), the response to lithium treatment, and other subclinical characteristics in a cohort of BD patients using a range of techniques. Initially, we looked into the relationship between the reaction to lithium and crucial candidate genes that have previously been found to affect the response to lithium in different populations. To identify genomic regions that showed different methylation patterns in lithium responders compared to non-responders, a global and CpG island DNA methylation profiling was done in the second step of the approach. Third, to identify and characterize CNVs associated with both the effectiveness of lithium and the symptoms of BD, a genome-wide copy number variation (CNV) research was conducted. Ultimately, an untargeted plasma metabolomic profiling study revealed that patients with bipolar disorder had varying concentrations of several distinct metabolite species, depending on whether they reacted to lithium medication or not. The study’s findings are consistent with the theory that BD is most likely brought on by the dynamic dysregulation of numerous proteins, metabolic pathways, and gene regulatory networks, which is an indication of intricate issues within the system.